2021
DOI: 10.7759/cureus.13064
|View full text |Cite
|
Sign up to set email alerts
|

Social Behaviors Associated With a Positive COVID-19 Test Result

Abstract: Objective To compare the social behaviors of individuals who were tested positive for COVID-19 relative to non-infected individuals. Methods We sent COVID positive cases and age/gender-matched controls a survey regarding their social behaviors via MyChart (online patient portal). We called cases if they did not complete the electronic survey within two days. Data were collected from May to June 2020. Survey responses for cases without close contact and controls were compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…As reported elsewhere, the risk of transmission seemed to be higher if the infected close contact showed symptoms of COVID-19 [8]. Outside of the household, having a job involving contact with many different people during the day was associated with an increased risk, a finding that has also been reported by others [13]. Different job types have previously been found to be associated with COVID-19.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As reported elsewhere, the risk of transmission seemed to be higher if the infected close contact showed symptoms of COVID-19 [8]. Outside of the household, having a job involving contact with many different people during the day was associated with an increased risk, a finding that has also been reported by others [13]. Different job types have previously been found to be associated with COVID-19.…”
Section: Discussionsupporting
confidence: 75%
“…Other studies have also found that contact with a known person infected with SARS-CoV-2 is the main risk factor for infection [10,13,17,26]. Further, we found that cases were more likely to have had close contact within the household, where controls were more likely to have close contact at work.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Several other case-control studies of community determinants have been published. Early in the pandemic (May to June 2020), a case-control study conducted in Ohio and Florida, found no association between infection with SARS-CoV-2 and attending private or public gatherings or use of public transport [6].…”
Section: Discussionmentioning
confidence: 99%
“…By use of a case-control design, researchers have aimed to identify determinants, private and societal, for SARS-CoV-2 infection. Risk factors reported from previous studies include household overcrowding [3, 4], work in senior/health care [3, 5], work on-site [3, 4, 6, 7], foreign citizenship [3] and low education [3]. At the societal level, only few studies have been performed.…”
Section: Introductionmentioning
confidence: 99%